Comparison of the habitat conditions of peat-moss phytocoenoses dominated by Eriophorum angustifolium Honck. or Carex rostrata Stokes from mires in Western Poland - Gąbka, Maciej; Owsianny, Paweł M.; Sobczyński, Tadeusz (Biodiversity: Research and Conservation, 2007)
The presented phytosociological and habitat study concentrates on the moss phytocoenoses dominated by Eriophorum angustifolium or Carex rostrata, from 26 Sphagnum dominated peatlands adjacent to the lakes of the Wielkopolska region in Western Poland. Associations with these species dominate in the vegetation of the analysed mire configurations. 19 chemical parameters of surface water were analysed. Particular attention was paid to the determination of the habitat trophy and its indicators, the concentration of factors connected with the hardness of water, and the content of humic substances. Phytocoenoses with E. angustifolium appeared in habitats where the analysed water parameters took lower values and more narrow amplitudes than those of the phytocoenoses with C. rostrata. The most important factors differentiating these two types of phytocoenoses, turned out to be the following: water colour, conductivity, Mg, Na and dissolved SiO4. In conclusion, the appearance of phytocoenoses with C. rostrata was connected with habitats richer in nutrients and more advanced in the process of mineralisation than those of E. angustifolium.